2016
DOI: 10.1097/acm.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

From Impairment to Empowerment: A Longitudinal Medical School Curriculum on Disabilities

Abstract: Through this curriculum, first- and second-year medical students learned about the obstacles faced by individuals with disabilities and became better equipped to understand and address the concerns, hopes, and societal challenges of their future patients. This inclusive approach may be used to design additional curricula about disabilities for the clinical and postgraduate years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…7 Fortunately, in recent years, medical education has placed greater focus on development and integration of disability curricula, with examples including stand-alone sessions, 8 a blended curriculum on examination of neuromusculoskeletal disabilities, 9 and longitudinal curricula. [10][11][12] Among these, "Introduction to Disability and Health for Preclinical Medical Students: Didactic and Disability Panel Discussion" by Rogers et al is a stand-alone disability session available in MedEdPORTAL that explores disability within a sociocultural context and harnesses shared student reflection so that students can understand and develop their own attitudes. 8 A systematic review of health care providers' attitudes toward people with disabilities conducted in 2012 concluded that attitudes were generally favorable, but that that some students and health care providers experienced "discomfort or anxiety when challenged with the responsibility of treating a person with physical disabilities."…”
Section: Citationmentioning
confidence: 99%
“…7 Fortunately, in recent years, medical education has placed greater focus on development and integration of disability curricula, with examples including stand-alone sessions, 8 a blended curriculum on examination of neuromusculoskeletal disabilities, 9 and longitudinal curricula. [10][11][12] Among these, "Introduction to Disability and Health for Preclinical Medical Students: Didactic and Disability Panel Discussion" by Rogers et al is a stand-alone disability session available in MedEdPORTAL that explores disability within a sociocultural context and harnesses shared student reflection so that students can understand and develop their own attitudes. 8 A systematic review of health care providers' attitudes toward people with disabilities conducted in 2012 concluded that attitudes were generally favorable, but that that some students and health care providers experienced "discomfort or anxiety when challenged with the responsibility of treating a person with physical disabilities."…”
Section: Citationmentioning
confidence: 99%
“…10 One teaching strategy that was used and endorsed by several included studies was the idea of using patients as educators. 2,7,13,17 This allowed students to have direct clinical experience with patients similar to those they may treat in the future. 7,13 Findings from these studies indicated an improvement in students' mindset towards people with disabilities after exposure to patients as mentors.…”
Section: Effective Teaching Strategiesmentioning
confidence: 99%
“…2,7,13,17 This allowed students to have direct clinical experience with patients similar to those they may treat in the future. 7,13 Findings from these studies indicated an improvement in students' mindset towards people with disabilities after exposure to patients as mentors. 2,12,17 Two studies investigated the effect of home visits and showed that students who observed patients in their own homes reported an increase in their awareness and knowledge significantly.…”
Section: Effective Teaching Strategiesmentioning
confidence: 99%
“…El conocimiento sobre el concepto de discapacidad y la rehabilitación, de forma general, no hace parte de la educación médica de pregrado, por lo que cuenta con poca intensidad horaria y un contenido ineficiente en su enseñanza 9 . Es claro que el médico de forma constante, indiferente a su especialidad, se enfrenta en su práctica médica al paciente en situación de discapacidad de cualquier grado 10 ; también se ve enfrentado al requerimiento de rehabilitación y la prescripción de terapias; en consecuencia, es prioritario que todos los médicos adquieran un conocimiento básico acerca de la medicina física y rehabilitación (MF&R) 11 . Entre otras habilidades que son dominio de la MF&R se encuentra el conocimiento del sistema nervioso periférico y central y el sistema músculo-esquelético, lo cual es de enorme utilidad para la formación del médico general 12 .…”
Section: Educación En Rehabilitaciónunclassified